Alignment of plate-like particles in a colloidal dispersion under flow in a uniform pipe studied by high-energy X-ray diffraction - Qazi, S Junaid S (Langmuir : the ACS journal of surfaces and colloids, 2010)
High-energy angle-dispersive X-ray diffraction has been used to study the alignment of colloidal suspension of kaolinite particles in water as they flow along a pipe. X-rays with energies above 25 keV have a major advantage, as they can penetrate through thick samples and walls of containers and permit investigation of samples under realistic flow conditions. As an example of the method, flow through a circular cross-section pipe with an internal diameter of 5 mm has been studied: this is typical of industrial applications. The angular distribution of intensities of peaks in the diffraction pattern as a function of the location of the pipe in the X-ray beam provides information about the alignment of particles under flow. Order parameters have been calculated to describe the alignment and direction of orientation. It is observed that the particles align in the direction of flow with their flat faces parallel to the flow. The experimental results are compared with the calculations of the local strain rate that help to explain the onset of alignment of the particles